The way to and from school: a third place vector for children to learn? - Camponovo, Sara; Moody, Zoe (Swiss Journal of Educational Research, 2021)
Childhood Studies have shown that children do not only learn through formal or non-formal education, either at school or at home. They also learn in other settings and contexts through their own actions. Based on empirical data from an inter- and transdisciplinary research project on the way to and from school, this article highlights and questions the informal learning that children do in this space. Firstly, it shows how the way to school allows for both preparation and distancing from the roles expected at school and at home. Secondly, an analysis of children’s types of learning along the way to school, that are complementary to those carried out in the family and school spheres, is conducted.